The Role Of Physical Education Through football In Students Of Smp Negeri 2 Ampek Nagari - Dian Al Hakki; wilda welis; Roma Irawan; Ridho Bahtra (STKIP Singkawang, 2025)
Dribbling is a fundamental technical skill in soccer that determines a player’s ability to control the ball and bypass opponents. At SMP Negeri 2 Ampek Nagari, students participating in extracurricular soccer activities have shown relatively low dribbling ability, highlighting the need for effective training methods. This study aimed to examine the effects of two training types Ladder Drill and Ball Feeling and the role of agility in improving dribbling skills. A pseudo-experimental method with a 2 x 2 factorial design was applied, involving 40 students divided into four groups based on training type and agility level (fast or slow). Data was collected through pre- and post-tests of dribbling and agility across 16 training sessions. The results, analyzed using two-way ANOVA at a 0.05 significance level, revealed a significant effect of both training type and agility level on dribbling improvement (F = 8.417; p < 0.05), with the interaction contributing 41.2% of the variation. The group with high agility who received Ball Feeling training showed the greatest improvement (mean = 57.80), followed by the low-agility Ball Feeling group (mean = 54.90). In contrast, those trained with Ladder Drill showed lower improvement 42.70 for high agility and 45.30 for low agility. The Tukey test confirmed significant differences between training methods at both agility levels. The study concludes that Ball Feeling training is more effective than Ladder Drill, especially when paired with good agility. Coaches are recommended to emphasize Ball Feeling exercises to optimize young players’ dribbling development.